Georg Gerson - komponist og borger - Mondrup, Christian (Rambam. Tidsskrift for jødisk kultur og forskning, 2021)
Georg Gerson This article describes the life and work of the Danish composer Georg Gerson (1790-1825). Born into a wealthy Jewish family, he was predetermined for a career in trade and banking. Indeed, he did become a successful banker and was rewarded the title of Courtly Advisor for his financial efforts for the Danish Treasury, ruined in the Napoleonic Wars. Georg Gerson’s parents were aware of his musicality and ensured him the best musical education available. He went to Hamburg for his business education in the house of the cultured and enlightened merchants Fürst and Haller. The prominent Hamburg composer Andreas Romberg introduced Gerson to composing techniques and aesthetics and became his lifelong mentor. At his return to Copenhagen, the merchant and banker Joseph Hambro employed Gerson, soon making him his companion. As organizer, violin soloist and composer, Gerson engaged himself in the musical activities taking place in musical societies like the Musical Academy and the Society for the Promotion of Music. Most of his orchestral and chamber music was performed there. He was an estimated guest at the literary and musical salons, like those held by Friederike Brun, and he diverted the audience with his songs, some of which reflected liberal thoughts in conflict with the ruling absolutism. A prominent bourgeois, he could not appear in public as a professional artist but was considered a talented amateur in and after his lifetime.